1998
DOI: 10.1073/pnas.95.5.2664
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Prevention of renovascular and cardiac pathophysiological changes in hypertension by angiotensin II type 1 receptor antisense gene therapy

Abstract: Hypertension produces pathophysiological changes that are often responsible for the mortality associated with the disease. However, it is unclear whether normalizing blood pressure (BP) with conventional therapy is effective in reversing the pathophysiological damage. The duration and initiation of treatment, site of administration, and agent used all appear to inf luence the reversal of the pathophysiological alterations associated with hypertension. We have previously established that retrovirally mediated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 43 publications
2
75
0
Order By: Relevance
“…[23][24][25][26] We also showed that the human HO-1 gene can be expressed in adult SHR by injecting the retroviral vector LSN-HHO-1 into newborns, 19 a method used by others, for example, to overexpress or suppress angiotensin receptors. 27 In a previous study, long-term expression of human HO-1 resulted in attenuation of hypertension in SHR. 19 The present study builds on the previous findings and further attempts to elucidate the mechanisms that may contribute to the effect of HO-1 expression on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] We also showed that the human HO-1 gene can be expressed in adult SHR by injecting the retroviral vector LSN-HHO-1 into newborns, 19 a method used by others, for example, to overexpress or suppress angiotensin receptors. 27 In a previous study, long-term expression of human HO-1 resulted in attenuation of hypertension in SHR. 19 The present study builds on the previous findings and further attempts to elucidate the mechanisms that may contribute to the effect of HO-1 expression on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, PCR analysis of the vector DNA showed that the virus had disappeared by 30 days indicating that the long-term effect was due to exposure to antisense for the AT 1 -R at a critical period. In all respects, the SHR had become as normal as their normotensive controls (16). Retroviruses are appropriate for dividing cells but are limited by their lack of effect in non-dividing cells and therefore are not suitable for hypertension therapy in adults.…”
Section: Other Vectorsmentioning
confidence: 99%
“…10 -14 The vasoconstrictor gene inhibition strategy with AS in DNA in rAAV appears to be effective for reducing high BP in animal models of hypertension, including SHR, for at least 2 months. 26,42 Retrovirus delivery of AS AT 1 -R prevents hypertension from developing in young SHR 30,31 but may be limited to a developmental model because the vector infects only dividing cells. Eventually the development of these strategies could provide new antihypertensive options.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this had beneficial effects, and a repeat of the experiment showed that the AS AT 1 -R had prevented the development not only of hypertension but also of cardiac fibrosis. 31 Retroviruses are appropriate for dividing cells but are limited by their lack of effect in nondividing cells and therefore cannot be used for hypertension therapy in adults, although they may be useful for cardiomyopathy, restenosis, and vascular remodeling.…”
Section: Retroviral Vectorsmentioning
confidence: 99%